2008
DOI: 10.1143/jjap.47.8182
|View full text |Cite
|
Sign up to set email alerts
|

Linearized Augmented Plane Wave Band Structure Calculations and Dielectric Function of Layered TlGaSe2

Abstract: The electronic energy-band structure of the room temperature phase of the ternary layered TlGaSe 2 has been approached using linearized augmented plane wave (LAPW) method. Band structure and dielectric function have been calculated. This function has also been obtained in a wide range of photon energies from 0.76 to 6.5 eV by using spectroscopic phase modulated ellipsometry and a good agreement between the calculated and measured values has been observed. As derived from the used LAPW wave function set, the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…Recent calculations for TlGaSe 2 , belonging to the same TlMeX 2 family have shown for the most part 3D character of the electronic band structure. Therefore the fact that interlayer bonds are much weaker than intralayer ones is questionable as the reason underlying two‐dimensionality of the band‐gap exciton in TlInS 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent calculations for TlGaSe 2 , belonging to the same TlMeX 2 family have shown for the most part 3D character of the electronic band structure. Therefore the fact that interlayer bonds are much weaker than intralayer ones is questionable as the reason underlying two‐dimensionality of the band‐gap exciton in TlInS 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In the past, a number of optical spectroscopy studies have been performed using these semiconductors under a convenient light direction normal to the ab plane; k || c, E ⊥ c. These studies revealed predominantly forbidden electron transitions and a close indirect and direct optical band gaps resulting from the weak covalent nature of the interlayer bonding [2][3][4][5][6][7][8][9]. In agreement with theoretical calculations of the electronic structure [6,9,10], the restriction of the band gap optical transitions comes from the fact that the bottom of the conduction band is mainly composed of Tl:6p orbitals whereas the top of the valence band of X:4p orbitals. The amount of states which symmetry forbids the transition in the dipole approximation is vastly larger in TlGaSe 2 than in TlInS 2 .…”
mentioning
confidence: 99%
“…Благодаря близости энергий прямых и непрямых зон эти кристаллы относятся к полупроводникам со смешанными типами краевого поглощения, что является следствием слабости сил осцилляторов, ответственных за эти переходы. Теоретический расчет зонной структуры этих соединений показал, что вершина валентной зоны формируется за счет волновых функций Se : 4p и Tl : 6s, в то время как дно зоны проводимости состоит из Tl : 6p-, Ga : 4s-и Se : 4s-состояний, которые показывают слабое отделение непрямой зоны [9,10]. Максимум валентной зоны лежит в Ŵ-точке зоны Бриллюэна, в то время как положение минимума зоны непрямых состояний, спорно.…”
unclassified
“…Минимум зоны непрямых состояний был найден теоретически в различных направлениях (Ŵ-Y) или (L−Z) линий в зависимости от расчетных приближений. Согласно [9,10], прямые и непрямые зоны разделены энергетически всего на 90 meV (Ŵ-Y); согласно работе [10], это энергетическое различие составляет 100 meV (Ŵ-Y); в [11] -50 meV (Ŵ-Y); согласно [12], 10 meV (L−Z). Авторы [9] в расчетах учли спин-орбитальное взаимодействие и в направлениях (Ŵ-Y) и (L−Z) было установлено, что минимумы непрямых состояний энергетически перекрываются.…”
unclassified